"Intestinimonas massiliensis" sp. nov, a new bacterium isolated from human gut. (January 2017) - Durand, G.; Afouda, P.; Raoult, D.; Dubourg, G.
Abstract: Here we report the main features of the proposed new bacterial species " Intestinimonas massiliensis " sp. nov. The type strain GD2 T (CSUR = P1930) was isolated from the gut microbiota of a healthy patient using a culturomics approach combined with taxonogenomics.